THE IMPACT OF ARTIFICIAL INTELLIGENCE ON EMPLOYMENT (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Artificial Intelligence (AI) is changing the job market, creating new types of jobs while automating routine tasks. With 20-50 million new jobs expected by 2030, AI is creating and enhancing jobs in healthcare, pharmaceuticals and other industries. While some industries may experience significant job displacement, the economy is expected to benefit from increased productivity and output. As AI continues to evolve, understanding its impact on employment and the economy is crucial. AI is rapidly transforming the workforce, with significant changes already apparent in the job market and employment landscape. As AI continues to develop and evolve, businesses and workers must adapt to stay competitive and efficient.